Enhanced Recovery after Thoracic Surgery - Martin, Linda W. (Seminars in Respiratory and Critical Care Medicine, 2020)
Enhanced recovery programs (ERPs) aim to reduce psychological and physiological stress related to surgery, and minimize opioid use. This article describes the tenets of enhanced recovery, the guidelines for ERP in lung surgery, and the University of Virginia experience with developing and implementing a program. The impact of these strategies on short-term patient outcomes and potential long-term benefits including influence on lung cancer-specific outcomes are reviewed. The opioid crisis is of utmost importance; this article will explore how ERPs may be a mitigating factor.
Keywords: enhanced recovery; lung cancer surgery; opioid reduction; rib block; outcomes